2021
DOI: 10.3389/fnins.2021.755870
|View full text |Cite
|
Sign up to set email alerts
|

The Etiology of Auditory Hallucinations in Schizophrenia: From Multidimensional Levels

Abstract: Enormous efforts have been made to unveil the etiology of auditory hallucinations (AHs), and multiple genetic and neural factors have already been shown to have their own roles. Previous studies have shown that AHs in schizophrenia vary from those in other disorders, suggesting that they have unique features and possibly distinguishable mechanisms worthy of further investigation. In this review, we intend to offer a comprehensive summary of current findings related to AHs in schizophrenia from aspects of genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 174 publications
1
8
1
Order By: Relevance
“…Therefore genetic factors related to hearing impairment may also contribute to risk of schizophrenia. Some previous studies have identified genes associated with auditory hallucinations, but none overlap with the proband-specific SV-containing genes identified in this study (Hugdahl et al, 2008;Shao et al, 2021). Furthermore, GWAS of common variants have found no evidence for enrichment of auditory-related pathways in schizophrenia (Trubetskoy et al, 2022).…”
Section: On Biological Pathwayscontrasting
confidence: 65%
“…Therefore genetic factors related to hearing impairment may also contribute to risk of schizophrenia. Some previous studies have identified genes associated with auditory hallucinations, but none overlap with the proband-specific SV-containing genes identified in this study (Hugdahl et al, 2008;Shao et al, 2021). Furthermore, GWAS of common variants have found no evidence for enrichment of auditory-related pathways in schizophrenia (Trubetskoy et al, 2022).…”
Section: On Biological Pathwayscontrasting
confidence: 65%
“…In conducting our review, we looked for studies examining schizophrenia-risk genetic variants that are parallelly implicated in both the development and dysfunction of language, and we also retrieved genetic studies specifically focused on FTD and AVHs in schizophrenia [154][155][156][157] . To systematically obtain the genetic variants that overlap between schizophrenia and language disorders, we first retrieved language-related genes from two recent reviews 158,159 .…”
Section: Genes Related To Schizophrenia and Languagementioning
confidence: 99%
“…Auditory hallucinations are a cardinal symptom of psychotic disorders, affecting more than two thirds of patients with a diagnosis of schizophrenia 1,2 . Hallucinations thus constitute one of the main diagnostic positive symptoms of schizophrenia spectrum disorders in the two major classification systems, in distinction of the usually longer-lasting and potentially more debilitating negative symptoms, such as cognitive decline, anhedonia, or flat affect 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Auditory hallucinations are a cardinal symptom of psychotic disorders, affecting more than two-thirds of patients with a diagnosis of schizophrenia. 1,2 Hallucinations thus constitute one of the main diagnostic positive symptoms of schizophrenia spectrum disorders in the two major classification systems, in distinction of the usually longerlasting and potentially more debilitating negative symptoms, such as cognitive decline, anhedonia, or flat affect. 3 However, auditory hallucinations are not pathognomonic for psychotic disorders, as they present with significant frequency (recent estimates ranging from 45% to 60%) in the context of a number of other mental disorders such as mood, dissociative, personality, and post-traumatic stress disorders, and may also affect approximately a third of patients with neurodegenerative disorders such as Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%